Legal Rules for Illegal Logging Perpetrators in Conservation Forests - Tjahjani, Joejoen; Mochtar, Mar'atul; Sastradinata, Dhevi Nayasari; Mahdiyah, Aisyah Nur (Universitas Islam Lamongan, 2026)
Illegal logging in conservation forests is an environmental crime that damages the ecosystem and the law. Illegal logging in conservation forest areas is a serious violation of forestry law provisions in Indonesia that has the potential to damage the ecosystem and forest conservation functions. Based on the description above, the problems to be studied in the study are: legal protection of conservation forests in laws and regulations in Indonesia and legal sanctions against perpetrators of illegal logging in conservation forests. The research method uses a normative juridical legal research type, so the approach used is the statute approach which includes primary legal materials: Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, Forestry Law Number 41 of 2013, Government Regulation Number 108 of 2015 also strengthens forest protection by prohibiting logging without a permit. From the results of the study, it can be concluded that the Enforcement of Legal Protection against conservation forests and legal sanctions against perpetrators of illegal logging in conservation forests is not only aimed at providing a deterrent effect through criminal sanctions and fines, but also maintaining the sustainability of forest functions as areas for preserving biodiversity and natural resources. Cases of illegal logging in conservation forests demonstrate the importance of synergy between law enforcement officers and communities to optimize forest protection and eradicate illegal logging practices.